Most commensally bacterial strains in human milk of healthy mothers display multiple antibiotic resistance - Huang, Mao‐Sheng; Cheng, Ching‐Chang; Tseng, Shu‐Ying; Lin, Yi‐Ling; Lo, Hui‐min; Chen, Po‐Wen (MicrobiologyOpen (Weinheim), 2019)
Recent reports have shown that food‐borne or commensal bacteria can function as reservoirs of antibiotic resistance. However, the antibiotic susceptibility of bacterial isolates of most milk samples or the total bacterial counts (TBC) in human milk from healthy donors, are not fully understood in Taiwan. Thus, five healthy mothers were randomly recruited each month, and totally 30 mothers without any symptoms of infection were recruited over 6 months. Milk samples were then harvested and analyzed immediately after collection. The antibiotic susceptibility was analyzed in bacteria isolated from milk samples using nine clinically relevant antibiotics, such as oxacillin, ampicillin, cephalothin, amoxicillin, ciprofloxacin, erythromycin, clindamycin, gentamicin, and oxytetracycline. The Staphylococcus strains (48 isolates) found in milk resisted to 48.6 ± 20.1% selected antibiotics. Streptococcus‐related isolates (8 isolates) exhibited resistance to 41.7 ± 26.4% selected antibiotics. Acinetobacter isolates (5 isolates) were resistant to 66.7 ± 13.6% antibiotics, and Enterococcus isolates (5 isolates) were resistant to 73.3 ± 6.1% tested antibiotics. Rothia‐related isolates (4 isolates) were resisted to 58.2 ± 31.9% of tested antibiotics. In contrast, Corynebacterium isolates (5 isolates) were sensitive to 66%–100% of selected antibiotics. Furthermore, the TBC ranged from 40 to 710,000 CFU/ml, implying a wide spectrum of bacteria in milk from healthy mothers. Despite this, all milk donors were healthy during sampling, and they did not show any symptoms related to mastitis or subclinical mastitis. According to the previously described TBC criteria for the use of donated human milk, only 73% of the current milk samples could be accepted for the milk bank. In conclusion, the majority of the isolated bacterial strains from current human milk samples are multiresistant strains. In milk samples for preterm infants or milk banks, higher TBC levels or potentially antibiotic‐resistant bacteria in some milk samples have supported people using approaches to disinfect human milk partially. Antibiotic sensitivity testing for Acinetobacter spp., Enterococcus spp. and Enterobacter of human milk from healthy mothers is shown. Acinetobacter isolates were resistant to 66.7% ± 13.6% tested antibiotics, and Enterococcus isolates were resistant to73.3% ± 6.1% tested antibiotics. These data suggested that Enterococcus spp. and Acinetobacter could more likely to confer a strong risk of antibiotic resistance in human milk samples worldwide.